PENDEKATAN PROJECT BASE LEARNIG PADA KONSEP FLUIDA DINAMIS, SISWA KLS XI IPA 3 SMA NEGERI 9 MANADO - Hermie Marasi (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
The quality of learning must be supported by the teacher's ability in learning. The problem is the teacher still places students as objects, not as subjects in classroom learning. The method used makes students just wait, do not take the initiative, or trying to be creative. The purpose of this action research is to improve the quality of learning by using the Project Base Learning approach to the concept of Dynamic Fluid. This type of research is action research on students of class XI IPA 3 Academic Year 2019/2020 SMA Negeri 9 Manado. The application of this learning base project is to obtain learning activities and outcomes that can be observed through behavior in the learning process and student test results. The results showed that in the first cycle students' learning outcomes and Student activities in this concept still did not meet the criteria. The second cycle shows high-grade learning results and student activities. The conclusion of the study attested that student activity experienced significant progress and fulfilment. It is recommended that in learning the concept of Dynamic Fluid the instructor should use the Project base Learning approach.